Effective state of polarization of photon-beam - Michalik, Łukasz; Domański, Andrzej (Photonics Letters of Poland, 2011)
In the paper a quantum description of an effective state of polarization for an electromagnetic field containing variously polarized photons is presented. The discussion of the problem includes the quantum character of a single photon, comparison with a classical field, matrix description of photon polarization and physical interpretation of the Pauli representation of a density operator that represents photons in a statistical ensemble. Full text: PDF References: R.J. Glauber, Quantum Theory of Optical Coherence (Wiley-VCH 2007). C.C. Gerry, P.L. Knight, Introductory Quantum Optics (Cambrige Univeristy Press 2005) R.J. Glauber, New Techn. Ideas Quant. Measur. Theory 480, 336 (1986). L. Michalik, J. Jasinski, P.L. Makowski, A.W. Domanski,"Problem of degree of polarization for photons", Proc. SPIE 7745, 77450K (2010). [CrossRef] T. Tudor, A. Gheondea, "Pauli algebraic forms of normal and nonnormal operators", Jour. Opt. Soc. Am. A 24, 204 (2007). [CrossRef]